2010
DOI: 10.1143/jpsjs.79sa.141
|View full text |Cite
|
Sign up to set email alerts
|

Structural Study of Ag–Ge–Se Superionic Glass

Abstract: Structural analysis of superionic glass Ag 0.5 (GeSe 3 ) 0.5 and in its molten state was performed by high-energy x-ray diffraction and neutron diffraction measurements at 110 and 300 K for the amorphous, 503 K for the supercooled-liquid state and 1223 K for molten state. Three-dimensional structural model at each temperature was obtained by means of reverse Monte Carlo (RMC) structural modelling on the basis of both diffraction data at 110 and 300K and X-ray data at 503 and 1223 K. It was revealed that the Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In our previous paper, temperature variation of structure for x=0.5 was studied associating with formation of ionic conduction path from molten state [3]. It was revealed that the Ag distribution in Ag 0,5 (GeSe 3 ) 0.5 has a tendency of forming chain-like fragments even in the molten state, which is characteristic feature in the Ag based superionic melts such as AgI [4] and Ag 2 Se [5].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In our previous paper, temperature variation of structure for x=0.5 was studied associating with formation of ionic conduction path from molten state [3]. It was revealed that the Ag distribution in Ag 0,5 (GeSe 3 ) 0.5 has a tendency of forming chain-like fragments even in the molten state, which is characteristic feature in the Ag based superionic melts such as AgI [4] and Ag 2 Se [5].…”
Section: Introductionmentioning
confidence: 96%
“…It was revealed that the Ag distribution in Ag 0,5 (GeSe 3 ) 0.5 has a tendency of forming chain-like fragments even in the molten state, which is characteristic feature in the Ag based superionic melts such as AgI [4] and Ag 2 Se [5]. The grown-up of medium-range order with decreasing temperature is related to the process of Ag ionic conduction path formation in the molten and supercooled liquid states [3]. However, micro phase separation has been recently reported by several researchers [6][7][8].…”
Section: Introductionmentioning
confidence: 98%
“…For a large range of Ag contents, the structural properties have been studied by Piarristeguy and coworkers by standard x-ray diffraction [3,4] and neutron diffraction [5]. Ohara, Kumara and coworkers analyzed the structure by means of highenergy x-ray scattering, neutron diffraction, and EXAFS [6,7], and most recently, our group discussed properties of the composition with 𝑥 = 0.50 by anomalous xray scattering and reverse Monte Carlo (RMC) modeling [20]. All studies agree that the average coordination number of silver is remarkably high, with a value of 3 or more.…”
Section: Introductionmentioning
confidence: 99%
“…A further structural investigation was carried out by the same group by ND and ab initio molecular dynamics (AIMD) simulation [6], where a strong evolution in the Ag-Ag correlations was observed in the Ag-Ag distance from the intermediate to short range with increasing the Ag concentration. Ohara and coworkers analyzed the structure by using high-energy XRD, ND, and EXAFS [7,8]. ND experiments with Ag isotope enriched samples were carried out by Zeidler et al [9,10] to clarify the role of Ag atoms.…”
Section: Introductionmentioning
confidence: 99%